(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the foundational aspects of Jalaluddin Rumi’s epistemology, focusing on both practical and conceptual dimensions of his understanding of knowledge. Rumi, as a Sufi philosopher and poet, viewed knowledge not merely as an intellectual pursuit but as a transformative journey of the soul toward divine truth. The study analyzes key elements such as intuition (kashf), spiritual experience, love (ishq), and the limitations of rationality in Rumi’s thought. It also examines the tension between conceptual reasoning and mystical insight, offering a philosophical interpretation of how Rumi reconciles experiential knowing with traditional forms of knowledge. The article contributes to a deeper understanding of Islamic philosophical mysticism and its relevance to contemporary debates in epistemology and spiritual philosophy.